Urban Perception: interlacement between Lucrécia Ferrara and Armando Silva´s thinking - Grossi, Virgínia Campos; Braida, Frederico; Abdalla, José Gustavo Francis (National Journal of City Management, 2021)
In face of the constant spatial, functional, social and symbolic changes in the city, understanding it beyond its physical aspects is the first step to discover its identity and how its spontaneous transformations take place. In this context, urban perception serves as theoretical and methodological support to understand the city and its subjective aspects. Identifying the relations between the user and the urban space, how the city expresses itself, its symbols and meanings present, go beyond the conventional, aesthetic and spatial understanding of the city to comprehend its relationships, its dynamics, and socio-space. Therefore, the article aims to discuss urban perception based on the theoretical contribution of two authors: Armando Silva and Lucrécia Ferrara. To seek analysis and possible reflections on the topic, the research presents as methodology a literature review focused on the study of the city from these two authors. Despite different directions, these researchers consider the city as a living organism in constant transformation, emphasizing, mainly, the perception of the inhabitants about the city as a research methodology. It was observed that, when considering a study of the city under a perceptive and multidisciplinary look, it escapes its traditional static reading and potentially reveals the cultural and social elements that characterize and identify it, allowing to comprehend the logic of spatial transformations from different points of view of different citizens.